“It just isn’t the same”: altered routines among older Americans three years after the COVID-19 pandemic onset - Rebecca A. Milan; Mallory A. P. Sagehorn; Mallory A. P. Sagehorn; Rohini Perera; Rohini Perera; Grace I. Bowman; Grace I. Bowman; Grace I. Bowman; Jessica Finlay; Jessica Finlay (Frontiers in Public Health)
IntroductionThe COVID-19 pandemic significantly disrupted civic life, particularly for older adults at increased risk for severe morbidity and mortality. Yet, little is known about the longer-term impacts on their daily routines and how this may affect health and wellbeing.MethodsThis qualitative study utilized data from older US adults who participated in the COVID-19 Coping Study’s three-year follow-up online survey, conducted in April–May 2023. The primary aim was to understand how and why daily routines have changed among older Americans (N = 1,309).ResultsParticipants had an average age of 71 years, with approximately 74% female and 93% identifying as Non-Hispanic White. We conducted content and thematic analysis of open-ended survey responses to identify five key reasons for still-altered routines 3 years after the pandemic onset: (1) COVID-19 risk and exposure, (2) altered access, (3) broader life circumstances, (4) emotional health, and (5) physical health.DiscussionThese findings highlight the enduring impacts of the pandemic on older adults’ routines and underscore the importance of integrating public health strategies that prioritize routine stability to enhance mental, physical, and social health. To support older adults’ wellbeing during and beyond public health emergencies, we recommend strengthening community-based programs, improving access to health and social services, and designing adaptable interventions that help individuals rebuild and maintain meaningful daily routines.